Cholera Public Health Campaign Writing Assignment - Kansas State University, K-State First (Kansas State University. K-State First., 2014)
Inspired by "The Ghost Map", this assignment asks students to answer essay questions about the book and design a public health campaign poster warning people of the dangers of cholera.
Keywords: Ghost Map, The; Writing assignment; Common reading program; Public health; Disease prevention; Papers (document genres)